System for open-chest, multidirectional electrical defibrillation - Viana,Marcelo Almeida (2016)
Abstract Introduction: Cardiomyocytes are more sensitive to stimulatory electrical fields when the latter are applied longitudinally to the cell major axis. In the whole heart, cells have different spatial orientations, which may limit the effectiveness of conventional electrical defibrillation (i.e., shock delivery in a single direction). This article describes the constructive aspects of a portable system for rapidly-switching, multidirectional stimulus delivery, composed of an electrical defibrillator and multielectrode-bearing paddles for direct cardiac defibrillation. Methods: The defibrillator delivers monophasic, truncated monoexponential waveforms with energy up to 7.3 J. Upon selection of the defibrillation modality (unidirectional or multidirectional), shock delivery is triggered through 1 or 3 outputs. In the latter case, triggering is sequentially switched to the outputs, without interval or temporal overlap. Each paddle contains 3 electrodes that define shock pathways spaced by 60°. The system was tested in vivo for reversal of experimentally-induced ventricular fibrillation in healthy swine, using 30- and 20-ms long shocks (N= 4 in each group). Results: The defibrillator delivers identical stimulus waveforms through all outputs in both stimulation modalities. In all animals, successful defibrillation required lower shock energy when 20 ms-long stimuli were applied in 3 directions, compared to a single direction. However, performance was poorer with multidirectional defibrillation for 30 ms-long shocks. Conclusion: The delivery of identical shock waveforms allowed confirmation that multidirectional defibrillation can promote restoration of sinus rhythm with lower shock energy, which may reduce myocardial electrical damage during defibrillation. Nevertheless, increase in shock duration greatly impairs the effectiveness of this defibrillation modality.